Managing the development of e-ID in a public e-service context: Challenges and path dependencies from a life-cycle perspective. Issue 1 (21st March 2016) - Melin, Ulf; Axelsson, Karin; Söderström, Fredrik
Abstract : Purpose: The purpose of this paper is to analyse and understand the contemporary management of electronic identification (e-ID) development to: identify and formulate challenges and reflect upon the use of a combination of perspectives. To generate knowledge on this issue, we investigate e-ID development in Sweden from: an e-government systems development lifecycle perspective and a project challenge and critical success factor (CSF) perspective. Design/methodology/approach: This is a qualitative case study covering an analysis of the three years in a larger project focusing e-ID in a public e-service setting. Empirical sources have been face-to-face interviews; official documents and different kind of forums for presentations and discussions in, for example, hearings arranged by authorities; meetings with the coordinating agency, and practitioners' networks events. Findings: This study concludes that there are significant challenges involved in managing e-ID development because of its contextual and integrated character. Challenges involve the organization and management of the program and can be traced back to e-government, general project management literature and theory on path dependency. Based on this study, we can question, e.g. governance models, centralization and a narrow focus on the technical artefact. Our study is also an illustration of a possible way to analyse e-ID within an e-government initiative. Research limitations/implications: The present study shows that an e-ID can be considered as a back office-enabler for launching e-services, but also highlights the need for management of the artefact as an integral part of e-service development because it is intertwined with the use of e-services from a user perspective. This aspect together with the insights related to challenges and success factors including path dependency provides implications for future practice of e-ID management and development in particular and information systems artefact development in general. Originality/value: This paper addresses challenges related to the development of e-ID in a public e-service setting. Few studies have theoretically combined a lifecycle perspective on challenges and success factors related to e-ID development while also focusing different dimensions of path dependency as an example of a challenging area within a program frame. Studying e-ID as a contemporary phenomenon from a contextual perspective in line with sociomaterial thinking – with a focus on the interplay between technology and people –can also help us to understand and discuss artefact development in general.